Modeling of the flow and heat exchange in pipes with turbulators of viscous heat carriers in the laminar region, as well as in the transition to turbulent flow - I. E. Lobanov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Mathematical modeling of heat transfer in pipes with turbulators for viscous heat carriers at Reynolds numbers characteristic of laminar and transient flow regimes is carried out by the calculation method. The solution of the heat exchange problem for semicircular cross-section flow turbulators based on multiblock computing technologies based on the solution of the Reynolds equations (closed for the transient mode using the Menter shear stress transfer model) and the energy equation (on multi-scale intersecting structured grids) by the factorized finite-volume method (FCOM) was considered.Method. The calculation was carried out on the basis of a theoretical method based on the solution of the Reynolds equations, closed for transient modes using the Menter shear stress transfer model, and the energy equation on multiscale intersecting structured grids (FCOM), by a factorized finite-volume method.Result. Both local and averaged characteristics of the flow and heat exchange in pipes with turbulators for a viscous coolant for laminar and transient flow modes of the coolant were obtained using the FCOM method in the work, which made it possible to determine for these modes the levels of heat exchange intensification that satisfactorily correlate with the existing experiment.Conclusion. The calculated relative hydraulic resistance for low turbulators increases quite slightly, and for medium-altitude turbulators reaches 2÷2.5 to the critical Reynolds number, and subsequently it increases up to 3 times; for high turbulators, the relative hydraulic resistance increases up to 4 times even before the transition flow regime is reached, after which it increases up to 4.5 times. The calculated relative isothermal intensified heat exchange under the laminar flow regime of a viscous coolant for relatively high turbulators increases almost 2 times; for relatively medium heights of turbulators — almost one and a half, and for low relative heights, the intensification of heat exchange is insignificant.